2017
DOI: 10.1136/jclinpath-2017-204484
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy interrogation of emergency medicine dispute cases: how often are clinical diagnoses incorrect?

Abstract: AimsEmergency medicine is a ‘high risk’ specialty. Some diseases develop suddenly and progress rapidly, and sudden unexpected deaths in the emergency department (ED) may cause medical disputes. We aimed to assess discrepancies between antemortem clinical diagnoses and postmortem autopsy findings concerning emergency medicine dispute cases and to figure out the most common major missed diagnoses.MethodsClin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 18 publications
2
18
0
5
Order By: Relevance
“…In addition, it’s important to identify the time of thrombus formation because it correlates with the time of death; thus, it is possible to evaluate with high probability if the clinical treatment has been corrected [12]. Several studies have evaluated the discrepancies between clinical and autopsy diagnoses, demonstrating that the use of different imaging techniques seldom contribute directly to inaccurate or missed diagnoses [1820]. Despite progress in imaging techniques and therapeutic treatment, the importance of autopsy remains crucial to elucidate the cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it’s important to identify the time of thrombus formation because it correlates with the time of death; thus, it is possible to evaluate with high probability if the clinical treatment has been corrected [12]. Several studies have evaluated the discrepancies between clinical and autopsy diagnoses, demonstrating that the use of different imaging techniques seldom contribute directly to inaccurate or missed diagnoses [1820]. Despite progress in imaging techniques and therapeutic treatment, the importance of autopsy remains crucial to elucidate the cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies comparing clinical diagnoses and autopsy findings revealed major discrepancies in approximately 10–40% of the deceased patients undergoing post-mortem examination [35]. Thus, complete diagnostic autopsy is an important tool for quality control of clinical practice [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for this decline have been discussed previously in literature [3,4,6] and include, among others, introduction of modern diagnostic tools in clinical practice. However, it is widely accepted that clinico-pathological discrepancies still occur even in the era of high-tech medicine [7,8,10], being much more frequent in low and middle income countries (LMIC), in which the availability of diagnostic techniques is limited [9]. Therefore, autopsies still have a crucial role in quality control of the clinical diagnosis and overall patient management.…”
Section: Introductionmentioning
confidence: 99%
“…Autopsije imaju značajnu ulogu u proceni kvaliteta zdravstvene službe, posebno službe hitne medicinske pomoći i jedinica intenzivne nege (JIN), kako internističke tako i hirurške [1]. Takođe, one omogućavaju lekarima uvid u adekvatnost primenjenih dijagnostičkih i terapijskih procedura i na taj način proširuju aktuelna znanja o različitim bolestima [1,2].…”
Section: Uvodunclassified